2013
DOI: 10.1002/acp.2989
|View full text |Cite
|
Sign up to set email alerts
|

The Passenger Effect: Risky Driving is a Function of the Driver‐Passenger Emotional Relationship

Abstract: This research focused on the influence of imaginary passengers on drivers' estimation of the probability of having an accident in traffic situations. Participants had to imagine riding a motorcycle with either a son or a workmate as a passenger. Their task was to assess the risk of accident in a set of traffic scenarios. Risk perception was a function of sex and type of passenger. Women perceived higher risk when the passenger was a son than when a workmate. In contrast, men's estimations were rather the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…of the protective factors against this behaviour. This could be explained in terms of the driverpassenger emotional relationship, as suggested by Megias and colleagues [73] who found that drivers perceived a higher level of risk when the passengers were their significant others (in particular children), as opposed to work colleagues. This finding should also be considered when designing campaigns against CPWD behaviour.…”
Section: Plos Onementioning
confidence: 95%
“…of the protective factors against this behaviour. This could be explained in terms of the driverpassenger emotional relationship, as suggested by Megias and colleagues [73] who found that drivers perceived a higher level of risk when the passengers were their significant others (in particular children), as opposed to work colleagues. This finding should also be considered when designing campaigns against CPWD behaviour.…”
Section: Plos Onementioning
confidence: 95%
“…It has been suggested that female drivers perceive the risks of driving with children as higher than males, which may motivate safer behavior (Megias et al 2014). According to the Koppel et al (2011) results, male drivers had significantly more overlong glances towards a child passenger than female drivers.…”
Section: Introductionmentioning
confidence: 99%